Butyrate ameliorates DSS-induced ulcerative colitis in mice by facilitating autophagy in intestinal epithelial cells and modulating the gut microbiota through blocking the PI3K-AKT-mTOR pathway - Ruifang Li; Yan Sun; Drolma Kelsang; Mingzhi Feng; Hanhui Cai; Jun Zhang (PLoS ONE, 2025)
Background Ulcerative colitis (UC) is an idiopathic, chronic inflammatory disease of the colon that imposes a significant global public health burden due to its recurrent and refractory nature. The therapeutic effects of butyrate on UC have been documented previously, but its specific mechanisms remain unclear. Objective This study aimed to investigate the effects and potential mechanisms of butyrate in dextran sulfate sodium (DSS)-induced UC. Methods A UC mouse model was induced utilizing 3% DSS, followed by interventions of 300 mg/kg, 600 mg/kg, or 1200 mg/kg of butyrate. The fecal condition and colonic pathology of the mice were observed, along with measurements of body weight and colon length. The expression of serum inflammatory factors, autophagy-related proteins, and the PI3K/AKT/mTOR pathway-related proteins were detected. Additionally, the impact of butyrate on the mouse gut microbial communities was evaluated using 16S rRNA sequencing technology. Results It was demonstrated that butyrate effectively alleviated UC symptoms, including bloody stools, weight loss, and colon shortening. Furthermore, butyrate reduced colonic tissue damage, decreased the expression of TNF-α, IL-1β, and IL-6, and significantly upregulated Beclin-1, Atg5, and the LC3II/I ratio, while reducing P62 expression. Butyrate also decreased the relative expression of p-PI3K/PI3K, p-Akt/Akt, and p-mTOR/mTOR. 16S rRNA sequencing results revealed that butyrate improved the intestinal microbial community structure by inhibiting harmful bacteria and accelerating the growth of beneficial bacteria. Conclusion This study suggests that butyrate may alleviate DSS-induced UC in mice by blocking the PI3K/AKT/mTOR pathway to facilitating autophagy in intestinal epithelial cells and by modulating the gut microbiota.